A Method to Retrieve Aeronomic Parameters From Noontime Bottom‐Side Equatorial Ne(h) and Satellite Neutral Density Observations - L. Perrone; A. V. Mikhailov (Space Weather, 2025)
Abstract A new method has been proposed to retrieve neutral composition ([O] [O2], [N2]), exospheric temperature (Tex), vertical ExB plasma drift, and total solar EUV flux (λ ≤ 1050Å) using Digisonde DPS‐4 daytime bottom‐side (≥200 km) Ne(h) profiles and satellite‐observed neutral density. The method is applicable around noon‐time hours at the geomagnetic equator under any geophysical conditions. A comparison of the retrieved EUV solar fluxes with TIMED mission EUV observations from 2002 to 2010 shows a mean relative deviation of approximately 3%. The inferred hmF2 values are consistent with Jicamarca Incoherent Scatter Radar (ISR) and Digisonde DPS‐4 observations. The proposed method effectively differentiates between various geophysical conditions by retrieving aeronomic parameters specific to particular events, as demonstrated for a counter electrojet event and a severe geomagnetic storm. The inferred ExB vertical plasma drifts were validated using ground‐based magnetic field H‐component observations. Overall, this method can be considered as a valuable tool for analyzing the equatorial thermosphere and ionosphere under different geophysical conditions.